Synthesis and Characterization of Nanocrystalline Zeolite Y - Ahmedzeki, Nada S.; Yilmaz, Selahattin; Al-Tabbakh, Ban A. (Al-Khwarizmi Engineering Journal, 2017)
Worldwide attention is being focused on nanocrystalline zeolites and they are replacing conventional ones due to their pronounced potential in many fields. In this study, NaY zeolite has been prepared hydrothermally using sol –gel method and modified to the proton type by ion –exchange process. Characterization is made using X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), Atomic force microscopy (AFM), Brunauer –Emmet- Teller (BET) nitrogen adsorption method, Ammonia Temperature programmed desorption (NH3-TPD) and Scanning electron microscopy( SEM). The effect of aging time, silica to alumina ratio is studied and the results show well defined crystalline structure with nano particle size (70 and 81nm) with surface area of 499m2/gm.